Economic Burden of Endometriosis: A Systematic Review and Meta-Analysis - Yuspa, Ripandi (Ikatan Dokter Indonesia Wilayah Jawa Timur, 2024)
Introduction: Endometriosis, marked by uterine-like tissue growth outside the uterus, causes severe pelvic pain and infertility. Delayed diagnosis contributes to its significant global economic burden, especially in Europe and the USA. Despite treatment advances, managing endometriosis remains challenging. Comprehensive strategies are urgently needed to reduce its economic impact and improve patient outcomes. Material and Methods: We searched for English-language full-text literature from PubMed, Cochrane, Wiley Library, and ScienceDirect databases from January 2013 to January 2024. Total of 951 studies were identified, and 14 studies were included, providing comprehensive data on the economic burden of endometriosis, including direct healthcare costs and productivity losses. Results: The economic burden of endometriosis, based on 14 studies, is substantial, reflecting both direct healthcare costs and productivity losses. Average annual costs per woman ranged from EUR 8,768 in Sweden to Int 16,970-20,898 in Australia. Non-surgical treatments in the USA were more cost-effective than surgery, costing 100,000 per QALY. In the UK, the LNG-IUS was the most expensive treatment at £650.94. Costs in China for various therapies ranged up to 10,728 with differing ICERs. Conclusion: These findings underscore the significant economic impact and the need for cost-effective management strategies: costs and productivity losses. Effective management strategies are essential to mitigate these costs.